The Archaeology of the Battle of Vuelta de Obligado, Buenos Aires Province, Argentina - Ramos, Mariano Sergio (2014)
This paper presents the results of research carried out for more than a decade at Vuelta de Obligado, San Pedro, north-east of Buenos Aires province. The objectives were to understand the dynamics of the strategy followed on the 1845 battlefield by the two groups who fought (Anglo-French and Argentine), and to assess the impact of formation processes on the results produced. This has been achieved through the use of several sources of information: the archaeological record, written documents, Argentine and European plans and sketches, as well as data provided by the current population.